2012
DOI: 10.1017/s003118201200114x
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and biochemical characterization of two closely related triosephosphate isomerases fromTrichomonas vaginalis

Abstract: The glycolytic enzyme triosephosphate isomerase catalyses the isomerization between glyceraldehyde 3-phosphate and dihydroxyacetone phosphate. Here we report that Trichomonas vaginalis contains 2 fully functional tpi genes. Both genes are located in separated chromosomal context with different promoter regulatory elements and encode ORFs of 254 amino acids; the only differences between them are the character of 4 amino acids located in α-helices 1, 2 and 8. Semi-quantitative RT-PCR assays showed that tpi2 tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…TvTIM is encoded by two genes (tvtim1 and tvtim2) (23), a feature associated with expression divergence in other organisms (36,37). Although the nucleotide sequences of the two tvtim genes are 97.6% identical, our results showed that they were differentially expressed in response to glucose (tvtim1 was negatively regulated, whereas tvtim2 was positively regulated) (Fig.…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…TvTIM is encoded by two genes (tvtim1 and tvtim2) (23), a feature associated with expression divergence in other organisms (36,37). Although the nucleotide sequences of the two tvtim genes are 97.6% identical, our results showed that they were differentially expressed in response to glucose (tvtim1 was negatively regulated, whereas tvtim2 was positively regulated) (Fig.…”
Section: Discussionmentioning
confidence: 70%
“…To obtain cDNA, 5 g of total RNA was treated with DNase I (3 U) and reverse transcribed using a RevertAid first-strand cDNA synthesis kit (Thermo Scientific-Pierce, Rockford, IL) and oligo(dT) primers, as recommended by the manufacturer. For PCR amplification, 500 ng of cDNA, Taq DNA polymerase (Invitrogen), and primers specific for the reported sequences in TRICHDB for the tvtim1 (TVAG_497370) and tvtim2 (TVAG_096350) genes were used, as previously described (23). The tvtim1 primers were 5=-ACATTCTTTGTCGGAGGC-3= (sense) and 5=-AATGTTGATGAAA CCTGG-3= (antisense), and the tvtim2 primers were 5=-ACATTCTTCG TCGGTGGT-3= (sense) and 5=-AATGTTGATGAAGCCTGG-3= (antisense).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations